Harry Potter and the Unconscious Dimension - Pyle, Mary Jerram (Trinity College Dublin. School of English. Discipline of English, 2022)
In this thesis I explore the extent to which an unconscious response on the part of the reader may contribute to the extraordinary popularity among both children adults of J. K. Rowling’s Harry Potter series (1997—2007). While there have always been books shared between children and adults, with this series the crossover phenomenon has become so significant that Bloomsbury published the text in different covers for children and adults. The series has attracted considerable critical attention, but this thesis breaks new ground by examining the unconscious elements behind the continued appeal of the Harry Potter series. I argue that as well as all the conscious reasons expressed for enjoying the books – good plots, characterisation, lively narrative and inventiveness — there is an unconscious element to readers’ enjoyment of the series. As the interest in and study of children’s literature as a discipline in itself has grown, so psychoanalysis has turned its focus on this subject. Stories and psychoanalysis are closely related: the patient on the couch tells a story to which the analyst listens; the author tells a story to which the reader listens. While literary criticism largely engages with the Lacanian theory of psychoanalysis, probably because both disciplines share an interest in language, my position lies within the Independent Tradition, a development of Klein’s theory of object relations. Klein refers to ‘positions’ rather than stages of development: we all move in and out of those positions throughout life. My clinical work is based on this theory, especially as interpreted by Donald Winnicott and Wilfred Bion and expanded by contemporary psychoanalysts, Antonino Ferro, Giuseppe Civitarese and Thomas Ogden among others. I use my psychoanalytical knowledge to analyse some of the issues that we all have to deal with throughout life, issues which push us into those positions, sometimes many times, not only in childhood, and to see where Rowling’s narrative illuminates these. I argue that by using this approach it is possible to throw light on the way in which readers of all ages can identify with Rowling’s characters. Although there are a few papers analysing the series from this position, this is the first full study of Rowling’s work in these terms. My thesis makes an original contribution to the dialogue between psychoanalysis and literature. The thesis begins with play and Winnicott’s assertion that play is at the base of all learning and emotional development. Rowling’s series is itself unique in that the most important theme running through the series is the theme of death. This theme is present from the beginning of the first book: although distanced by time it is not initially clear to readers that it is the precipitating event as well as being the central topic. I explore the topic of death in the final chapter of this study, and posit that although the response of readers may be largely unconscious, her treatment of the topic is the underlying reason for the phenomenal popularity of the series. Other themes to which readers respond both consciously and unconsciously are the development of the protagonists from eleven-year-old children to adult, and the struggle between good and evil, both of which are themes which run through the series from beginning to end. Chapter 4 on the Quest acknowledges the symbolism of the quest narrative which has been popular from earliest literature and also explores the significance and symbolic meaning of the various stopping places on Harry’s quest. The quest and alchemy both address development through acquiring experiential knowledge leading to personal and social transformation of the protagonists. This thesis offers a new and innovative way to read the Harry Potter series, demonstrating that an interdisciplinary approach combining literary studies with psychoanalysis enables to uncover the hidden and unconscious element behind readers’ enjoyment of the books.
APPROVED
Keywords: children's literature; fantasy; psychoanalysis; alchemy; death; transcendence